Inner ear modifications in Dar-es-Soltane II H5 (Morocco): A case of labyrinthitis ossificans - Coutinho-Nogueira, Dany (2022)
Objective: This paper presents the inner ear modifications in Dar-es-Soltane II H5, an Aterian fossil possibly dated to 100 ka. Material: The remains consist of a large portion of the cranium including the face, the left frontal and temporal bones, part of the left parietal bone and greater wing of the sphenoid. Methods: The bony labyrinth anatomy was investigated on existing micro-CT data acquired by the MPI-EVA. Results: The observation of micro-CT sections revealed a partial filling of the semi-circular canals that raises question about its origin. A careful examination of the micro-CT sections shows that the elements present in the semicircular canals were denser than the sediments observed in other regions and cavities of the temporal bone. Conclusions: The current evidence suggests a pathological origin of this condition with partial ossification of the membranous labyrinth. The differential diagnosis indicates a case of labyrinthitis ossificans in its early stages. Significance: This pathological condition can be responsible for permanent hearing loss and is associated with dizziness and vertigo. Along with the Singa skull, Dar-es-Soltane II H5 represents one of the oldest known cases of labyrinthitis ossificans. Limitations: The early stage of disease and the absence of the right temporal bone limit conclusions about the degree of disability of the individual and their dependence on the rest of the group. Suggestions for further research: To carry out a paleopathological study of all the fossils from Dar-es-Soltane II.